Tree seedling shade tolerance arises from interactions with microbes and is mediated by functional traits - Wood, Katherine E. A.; Kobe, Richard K.; McCarthy-Neumann, Sarah (Frontiers in Ecology and Evolution, 2023)
Shade tolerance is a central concept in forest ecology and strongly influences forest community dynamics. However, the plant traits and conditions conferring shade tolerance are yet to be resolved. We propose that shade tolerance is shaped not only by responses to light but also by a species' defense and recovery functional traits, soil microbial communities, and interactions of these factors with light availability. We conducted a greenhouse experiment for three temperate species in the genus Acer that vary in shade tolerance. We grew newly germinated seedlings in two light levels (2% and 30% sun) and controlled additions of microbial filtrates using a wet-sieving technique. Microbial filtrate treatments included: <20 µm, likely dominated by pathogenic microbes; 40-250 µm, containing arbuscular mycorrhizal fungi (AMF); combination, including both filtrate sizes; and sterilized combination. We monitored survival for nine weeks and measured fine root AMF colonization, hypocotyl phenolics, stem lignin, and stem+root nonstructural carbohydrates (NSC) at three-week intervals. We found that differences in seedling survival between low and high light only occurred when microbes were present. AMF colonization, phenolics, and NSC generally increased with light. Phenolics were greater with <20 µm microbial filtrate, suggesting that soil-borne pathogens may induce phenolic production and NSC was greater with 40-250 µm filtrate, suggesting that mycorrhizal fungi may induce NSC production. Across species, microbe treatments, and light availability, survival increased as phenolics and NSC increased. Therefore, shade tolerance may be explained by interactions among soil-borne microbes, seedling traits, and light availability, providing a more mechanistic and trait-based explanation of shade tolerance and thus forest community dynamics. This is a provisional file, not the final typeset article responses to light availability alone (Valladares and Niinemets, 2008;Valladares et al., 2016). Understanding the functional traits and biotic and abiotic conditions that convey shade tolerance are key to a more mechanistic understanding of forest community dynamics. A plant's ability to tolerate low light conditions can be moderated by soil-borne microbes, like soilborne pathogens and mycorrhizal fungi (Jiang et al., 2020). Soil-borne pathogens (including fungi, oomycetes, and bacteria) can cause high seedling mortality (